'Aversive' democracy, 'contentious' politics and 'agonistic' populism: comparative experience and implications for contemporary North Africa. Issue 6 (1st November 2020) - Whitehead, Laurence
ABSTRACT: There is a vast social science literature on the politics of protest and 'bottom up' mobilisation. One strand concerns peaceful protest is stable constitutional systems. Another deals with revolutionary mobilisation to overthrow repressive regimes. This article focuses on an intermediate cluster of recent contributions of more direct relevance to today's Maghreb. These all concern mass movements seeking more inclusive democratic dispensations. Such mobilisations are voluntary and pluralist in spirit (not revolutionary) and so favour peaceful and inclusionary forms of expression. 1 But they confront regimes that lack constitutional legitimacy, and that in their insecurity may react with arbitrary repression. So these processes involve acute uncertainty and intense risk for participants. Three main approaches are outlined and compared. Aletta Norval draws from her South African experience in her formulation of ideas about 'aversive' democracy. Sidney Tarrow and Charles Tilly have produced ground breaking work on 'contentious' politics that partly reflects their base in the USA. The Essex school inspired by Ernesto Laclau and Chantal Mouffe is more attuned to Latin American and some European experiences of 'agonistic' mobilisation. While all three approaches have important ideas to contribute, each also displays conceptual and empirical limitations. This article aims to highlight the useful insights of each, and provide some guidance about how well they 'travel' to North Africa, and how lessons from this region might be fed back into the global debate about 'informal' political activism in the twenty-first century.